Alterations in Microbiota-Gut-Brain Axis and Susceptibility or Resilience to Traumatic Stress - Tanelian, Arax; Nahvi, Roxanna; Nankova, Bistra; Sabban, Esther (The FASEB journal, 2022)
Post-Traumatic Stress Disorder (PTSD) is a severe and long-lasting outcome of exposure to traumatic life event. Exposure to trauma induces PTSD only in a sub-population of individuals while others remain resilient. The mechanisms and contributing factors differentiating between stress resilient and stress susceptible subjects are still unclear. We hypothesize that inter-individual differences in the microbiome composition and its function contribute to host resilience or susceptibility to stress induced psychopathologies. The current study aimed to characterize differences in the gut microbial community structure and function that mediate vulnerability or resilience to traumatic stress in the Single Prolonged Stress (SPS) animal model of PTSD. Sprague-Dawley male rats were divided into unstressed controls and SPS experimental group. After 14 days, behavioral analyses were performed using Open Field, Social Interaction and Elevated Plus Maze tests. Based on the anxiety measures, the SPS group was further subdivided into SPS-resilient (R) and SPS-susceptible (S) subgroups. After the last behavioral test, the animals were sacrificed and cecum, colon, hippocampus, and medial prefrontal cortex were collected. Prior to SPS and immediately after Open Field test, fecal samples were collected from each rat for 16S V3-V4 ribosomal sequencing; whereas urine samples were collected before SPS, 90 minutes into immobilization and on the day of dissection to measure urinary epinephrine (epi) and norepinephrine (norepi) levels. Analyses of the fecal microbiota revealed significant differences among the groups before and after SPS stressors. Before SPS, the SPS-S subgroup harbored microbiota with an overall pro-inflammatory phenotype, such as significantly increased levels of Clostridia, and decreased levels of Lactobacillusand Barnesiella compared to the SPS-R subgroup. After SPS, among the many changes observed were significant shifts in the abundance of Firmicutes and Bacteroidetes in SPS subgroups. Urinary epi and norepi levels were also different among the groups, with SPS-S subgroup having higher baseline catecholamines levels. In line with the alterations seen in the gut microbiota, the levels of cecal short chain fatty acids were also altered, with SPS-S subgroup having significantly lower levels of Acetate, Valerate and Caproate. Interestingly, the levels of acetate inversely correlated with anxiety index. The colon length and permeability were also altered, with SPS-S having significantly shorter colon and increased permeability as measured by Claudin-1 expression. Finally, analyses of different brain regions also revealed significant increases in blood brain barrier permeability in SPS-S subgroup as determined by Claudin-5 expression. Taken together, our results suggest microbiota is a potential factor in predisposing subjects either to stress susceptibility or resilience. Moreover, SPS triggered significant shifts in the gut microbiota, their metabolites and brain and gut permeability. These findings could lead to new therapeutic directions for PTSD possibly through the controlled manipulation of gut microbiota. It may enable early identification of individuals more likely to develop prolonged anxiolytic symptoms following traumatic stress.